Unconstitutionality of article 83 the organic law on the management of identity and civil data that privaces people from the human right to identity - Sanipatin Mora, Gabriela Alexandra (SATHIRI, 2021)
The authorities, servants and public servants of the Civil Registry and Identification Service of Ecuador, are empowered by Art., 83 of the Organic Law of Identity and Civil Data Management, in the case of a double or multiple registration of the same act or fact of the civil status of people, despite the fact that they contain different data, in order to cancel subsequent registrations. But these annulments have also led the annulment of the human right to identity, a situation which contravenes the international human rights instruments that enshrine it, as the Universal Declaration of Human Rights and the Convention on Human Rights, both of the Organization. of the United Nations, as well as the Constitution of the Republic and the Childhood and Adolescence Code. 66 of the aforementioned constitutional body provides that the right to personal identity includes preserving, developing and strengthening the material and immaterial characteristics of identity, including nationality and family origin. Which, when birth registration is annulled, disappear administratively, which is unconstitutional because there is a conflict between norms of higher and lower hierarchy, which the Constitution of the Republic itself resolves in paragraph 2° of its Art.